INFLUENCE OF FAMILY ENVIRONMENT AND PEER PRESSURE ON CRIMINAL TENDENCIES AMONG UNDERGRADUATE STUDENTS OF FEDERAL UNIVERSITY OF LAFIA, NASARAWA STATE, NIGERIA - Abubakar, Suleiman Aliyu; Aliyu, Abdullahi Oyiwose; Babayo, Sulaiman; Zakariya, Yakubu Angyo; Muhammad, Zubairu Aliyu; Enneh, Asheson Bernard; Allahnana, Rukaiyat (African Journal of Social and Behavioural Sciences, 2023)
The study investigated the influence of family environment and peer pressure on criminal tendencies among Undergraduate Students of Federal University of Lafia, Nasarawa State. Three hundred and nine-one participants with ages ranging from 17-28 years (Mean= 18.69; SD=9.52) were selected from different departments of the institution using simple random sampling technique. Cross-sectional survey design was adopted for the study. Three hypotheses were formulated and tested using Simple Linear Regression and Multiple Regressions analysis. Simple Linear regression and multiple regression indicated that there was a positive relationship between family environment and criminal tendency (R = 0.793 = R2 = 0.542 (F (1,390) = 184.184, t = 14.260, p < .05). Further analysis revealed that peer pressure significantly influenced criminal tendency (R = 0.576 = R2 = 0.153 (F (1,390) = 24.630, t = 6.706, p < .05). Also, result of hypothesis three indicated a significant relationship between family environment and peer pressure on criminal tendency (R = 0.835 = R2 = .610 (F (2, 389) = 106.487, t = -5.087, p < .05). It was recommended among others that; parents should be mindful of the kind of peers their children/wards associate with because they can learn bad behaviours from them.